2018
DOI: 10.1038/s41467-018-05197-2
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 targets L-selectin for adhesion and induces its shedding for viral release

Abstract: CD4 and chemokine receptors mediate HIV-1 attachment and entry. They are, however, insufficient to explain the preferential viral infection of central memory T cells. Here, we identify L-selectin (CD62L) as a viral adhesion receptor on CD4+ T cells. The binding of viral envelope glycans to L-selectin facilitates HIV entry and infection, and L-selectin expression on central memory CD4+ T cells supports their preferential infection by HIV. Upon infection, the virus downregulates L-selectin expression through she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(48 citation statements)
references
References 68 publications
3
44
0
Order By: Relevance
“…We have shown that L-, Pand E-selectins bind to purified EBOV-GP coated on ELISA plates and to EBOV-GP transfected cells (HEK-293 and CHO-K1). This is confirmed by recently published data that the viral particle gp120 of HIV-1 binds L-selectin (CD62L) (84)(85)(86)(87). Similarly, human P-selectin glycoprotein ligand-1 is a functional receptor for enterovirus 71 (180).…”
Section: Ebov-gp Protects Hek-293 Cells From Lysis By Polyclonal Nk Csupporting
confidence: 78%
See 2 more Smart Citations
“…We have shown that L-, Pand E-selectins bind to purified EBOV-GP coated on ELISA plates and to EBOV-GP transfected cells (HEK-293 and CHO-K1). This is confirmed by recently published data that the viral particle gp120 of HIV-1 binds L-selectin (CD62L) (84)(85)(86)(87). Similarly, human P-selectin glycoprotein ligand-1 is a functional receptor for enterovirus 71 (180).…”
Section: Ebov-gp Protects Hek-293 Cells From Lysis By Polyclonal Nk Csupporting
confidence: 78%
“…We conclude that selectins play an important role in virus release from infected cells, as it has been shown for HIV, which binds L-selectin and CD34 to co-localize with ADAM17 (84)(85)(86)(87). Glycans designated sialyl 6-sulfo Lewis x carbohydrate are potential ligands for selectins [15].…”
Section: Ebov-gp Protects Hek-293 Cells From Lysis By Polyclonal Nk Cmentioning
confidence: 59%
See 1 more Smart Citation
“…Such post-translational mechanisms of reducing L-selectin surface expression by HIV is thought to prevent trafficking back to secondary lymphoid organs, redirecting infected T-cells to the systemic circulation to increase viremia. L-selectin expression on naive CD4 T-cells has recently been defined as a novel receptor for HIV entry (58), and work from this study reveals that L-selectin shedding ensues 4–6 days post-infection. Moreover, HIV preferentially infects T CM over T EM cells – positively correlating with L-selectin expression.…”
Section: Regulation Of L-selectin Protein Expression In Divergent Leumentioning
confidence: 77%
“…In addition, some Siglecs—Siglec‐3 both on HL‐60 and on granulocyte, Siglec‐5 and Siglec‐9 on granulocyte—were found. L‐Selectin, which is involved in migration of leukocytes, generally recognizes sialyl Lewis oligosaccharide structures on glycoproteins and/or glycolipids and interacts weakly with sialyl lactose . On the other hand, Siglecs, which are involved in cell–cell interaction and immune response, recognize sialyl oligosaccharide structures containing SAα2‐3Gal and SAα2‐6Gal motifs .…”
Section: Resultsmentioning
confidence: 99%